ILRI 40 years remarks by Manuel Flury, Director of Cooperation, SDC, Ethiopia - Flury, M. (International Livestock Research Institute, 2014)
Remarks from Manuel Flury, Director of Cooperation, Swiss Agency for Development and Cooperation in Ethiopia (representative of an ILRI founding institution) at the ILRI@40 Conference: Livestock-based options for sustainable food and nutritional security, economic well-being and healthy lives. ILRI@40 conference, Addis Ababa, Ethiopia, 6–7 November 2014.